THE DEVELOPMENT OF THE INTERNAL EDGE PASS TECHNIQUE APPLIED IN WOMEN’S FOOTBALL - Henry Nelson Cuasapas Bermeo, Elva Katherine Aguilar Morocho (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The techniques in soccer refer to the control of the ball, and require the development of perception, decision and execution mechanisms so that the players efficiently coordinate the different passes and fulfill the objective of winning the game, however, it is evident that the Players have difficulties in mastering the pass with the inside edge, affecting their performance in the team, which is why the question arises: How does the development of the passing technique with the inside edge influence the performance of the athletes? It proposes as an objective to analyze how the development of the passing technique with the inside edge affects the performance of the athletes. The methodology used in the study was under qualitative and quantitative approaches, experimental and descriptive; the study population consisted of 15 young people (14 years old). A pass precision test with 5 exercises was used as a study instrument, which allowed to diagnose the coordination in the athletes and to show the problem. The results showed that a percentage of soccer players have problems with mastering the pass with the inside edge, which affects the performance of the team, being necessary to plan exercises aimed at improving coordination and passing the inside edge, apply them in training, and improve the team's performance on the court. It is concluded that the passing technique with the inner edge is a necessary complement for the soccer players to perform a better team game.